Proposal for the testing of a tool for assessing the risk of dehydration in the elderly patient - Bulgarelli, Ketty (Acta Biomedica Atenei Parmensis, 2015)
Background: Dehydration is now the most common fluid and electrolyte disorder in older people. Because it is often associated with high rates of morbidity and mortality, it requires careful control and prevention in the context of a thorough primary care. The main risk factor for dehydration was the low intake of water by mouth for several reasons, such as lack of autonomy, altered mental status, decreased sensation of thirst, social and environmental problems. To this may be added an increase in fluid loss caused by fever, vomiting, diarrhoea, bleeding etc., the use of diuretics or laxatives and the onset of diseases that induce an increase in the loss of urine (e.g. diabetes). This paper aims to locate a tool for assessing the risk among those reported in the literature that is easy to use for the nurse and to experiment with it on a sample of patients. Methods: An analysis of the literature showed the reliability of an instrument for assessing the risk of dehydration by the name of “Dehydration Risk Appraisal Checklist.” In order to verify its usefulness in identifying the risk of dehydration, 2 groups of elderly persons at the OU Geriatrics and long-term care unit of the Azienda USL of Piacenza and the OU complex Geriatric Clinic of the University Hospital of Parma were investigated. Patients in both groups were assessed on admission by the assessment scale MNA (Mini Nutritional Assessment) and by the sheet of quantitative evaluation of the meal consumed. One group was considered as the “control group”. Patients belonging to the other group, which was regarded as the “experimental group”, in addition to the two above-mentioned instruments, were also assessed by the “Dehydration risk appraisal checklist”. In both groups, the presence or absence of four indicators of dehydration measured at the time of and immediately before discharge was then detected. In the presence of each indicator of dehydration one point was awarded for a comprehensive evaluation. The data collected were analyzed using a statistical method. Results and Conclusions: The results showed no statistically significant differences in the identification of the risk of dehydration in the two groups. It is believed, however, that the data will guide checklists to consider the above-mentioned instrument valid and useful in nursing practice in order to assess the risk of dehydration in older people and early detection of its onset and thus enable prompt and effective management. It will take more extensive studies of case studies to test this hypothesis.